A Qualitative Study on the Contemporary Perspectives and Experiences of Co-residence During COVID-19 Among “Boomeranging” Young Adults and Their Mothers in England - Katrina Messiha; Gillian Stokes (SAGE Open)
The “Boomerang Effect” (BE) is a contemporary phenomenon in England and wider Europe, referencing young adults who move out of their parents’ home to live independently but eventually return to live with their parents again. Despite concerns about residential independence and the intensification of BE due to the COVID-19 pandemic, there is limited qualitative data investigating it. This qualitative study utilizes diary methods to elicit the perspectives and experiences from six mother-young adult child dyads in England for 21 days to enable holistic and dynamic insights on the day-to-day exposures to the BE phenomenon. Findings resulted in several salient themes: (1) prime concerns shaping living arrangements, (2) framing of (participant) role, (3) conceptualization of [participant] identity, (4) nature of family relations, (5) depiction of independence, and (6) perceived situational input of Government. This work underscores the interdependent and complex relationship between structure and agency manifest in the BE context.